2016
DOI: 10.1002/2015wr018135
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of recycled moisture to precipitation in oases of arid central Asia: A stable isotope approach

Abstract: Terrestrial moisture contributed by surface evaporation and transpiration, also known as recycled moisture, plays an important role in hydrological processes especially across arid central Asia. The stable hydrogen and oxygen isotopes can be used for water budget analysis to calculate the contribution of recycled moisture to precipitation between two locations along the moisture flow. Based on a three-component isotopic mixing model, the moisture recycling in oasis stations of arid central Asia during summer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 53 publications
4
74
1
Order By: Relevance
“…In addition, the convective processes of the vortex also mean that locally recycled vapor may contribute more to precipitating vapor in atmosphere, and local moisture is usually isotopically depleted. Although the regional background is arid, the recycled moisture contributed from oases cannot be ignored [ Wang et al ., ; Li et al ., ] and the lakes of Eastern Kazakhstan may also contribute.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the convective processes of the vortex also mean that locally recycled vapor may contribute more to precipitating vapor in atmosphere, and local moisture is usually isotopically depleted. Although the regional background is arid, the recycled moisture contributed from oases cannot be ignored [ Wang et al ., ; Li et al ., ] and the lakes of Eastern Kazakhstan may also contribute.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, a 23‐station network for the measurement of stable isotopes in precipitation was established around the Tianshan Mountains in central Asia [ Wang et al ., ]. Recently, the regime of below‐cloud evaporation [ Wang et al ., ] and moisture recycling [ Wang et al ., ] in arid central Asia was assessed based on this event‐based database. This network provides a good platform to detect the impact of moisture source variation on stable isotopes in precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the precipitation recycling process is strong in western China, especially the Tibetan plateau and the surrounding areas, while being weaker in Southeast China due to the influence of summer monsoon. At large oases of Urumqi region of NW, the proportional contribution of recycled moisture to local precipitation is approximately 16.2% (Wang et al ., ). Some studies found that glacial retreat over the NW has increased significantly since the 1990s due to climate warming, and the increased glacial melt water has led to an increase in river runoff (Li et al ., ; Yao et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotopes (δ 18 O and δ 2 H) in precipitation provide important source signatures of different components of the hydrological cycle, including reevaporation (Salamalikis, Argiriou, & Dotsika, 2016;Wang, Zhang, Che, Zhu, & Liu, 2016), precipitation (Rahul, Ghosh, Bhattacharya, & Yoshimura, 2016;Wang, Zhang, Che, Chen, & Qiang, 2016), and moisture sources (Rangarajan, Laskar, Bhattacharya, Shen, & Liang, 2017;Strong, Sharp, & Gutzler, 2007). Global δ 18 O and δ 2 H levels in precipitation are monitored by the International Atomic Energy Agency to identify the relationship between atmospheric processes and isotopic signals in water vapour and precipitation (Angert, LEE, & Yakir, 2008;Jacob & Sonntag, 1991).…”
Section: Introductionmentioning
confidence: 99%